การเสนอวาระสาธารณะกรณีคัดค้านการแปรรูปการไฟฟ้าฝ่ายผลิตแห่งประเทศไทยในสื่อมวลชนและสื่อของสหภาพแรงงานฯ - นิศาชล ทวนทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The objectives of this research are: 1. to study the anti-privatization policy of the Electricity Organization of Thailand (EGAT) 2. to study the channeling of public agenda of EGAT s Labor Union in the mainstream media and the union s website, luegat, during the Thai Rak Thai government in 2004-2005. The research methods are; document research, depth interview, field observation and content analysis of news from television Channel 7, 9 and Nation Channel Thai Rath, Thai Post, Matichon and Krungthep Turakit. The study found that EGAT Labor Union s opposition to the government s privatization policy was because this would change EGAT public service mandate. The change will have serious effect on electricity rate and the security of the system. Dams and electricity infrastructure would be transferred from public asset into private hands. The Union also opposed the plan to bring the public enterprise in to the stock market and the conflict of interest incurred from this policy. The government responsed immediately to the agenda on electricity rate and distribution of shares. Second priority was given to the agenda on public asset. The mainstream media although welcomed the anti-privatization move by the Labor Union did not push far enough to win public consensus. Television Channel 7 and 9 gave more spaces to government and EGAT sources while Nation Channel inclined to give spaces to EGAT Labor Union. Thai Post, Matichon and Krungthep Turakit gave spaces to the anti-privatization groups whereas Thai Rath was compromised by government. EGAT Labor Union put up its website, www.luegatl.com, in a bid to oppose the privatization policy. This is a new type of citizen medium to channel its opposition agenda to EGAT s employees and union members, including civil society networks. The website worked as a channel to counter the government and administrative agenda by providing information and conscientize, as well as empower the readers. In addition, EGAT s Labor Union built its network around civil society as a strategy to strengthen the people s political movement. This means that the anti-privatization agenda has become part of a larger movement or the New Social Movement (NSM).